A MANAGEMENT COMMUNICATION CHANGE STRATEGIES IN THE CONTEXT OF GROUP COMMUNICATION - Annisa Febrina (Sean Institute, 2023)
This research seeks to analyze the communication behavior, process and influence of communication that takes place in the student community. The analysis was conducted qualitatively using the perspective of communication psychology related to community-based da'wah activities in rural areas. The results showed that the formulation of community da'wah was innovative and creative. The communication process takes place in the context of small group, large group, organizational and mass communication. This communication process takes place both face-to-face and in the media. The communication process affects communication behavior. The influence of communication behavior is in the form of conformity, social facilitation and polarization. These three changes in communication behavior occur in the aspects of knowledge, belief, ritual, experience and commitment.